Gliadin proteolytical resistant peptides: the interplay between structure and self-assembly in gluten-related disorders - Herrera, Maria Georgina (2021)
In recent years, the evaluation of the structural properties of food has become of crucial importance in the understanding of food-related disorders. One of the most exciting systems is gliadin, a protein in wheat gluten, that plays a protagonist role in gluten-related disorders with a worldwide prevalence of 5%, including autoimmune celiac disease (CeD) (1%) and non-celiac wheat sensitivity (0.5–13%). It is accepted that gliadin is not fully digested by humans, producing large peptides that reach the gut mucosa. The gliadin peptides cross the lamina propria eliciting different immune responses in susceptible patients. Many clinical and biomedical efforts aim to diagnose and understand gluten-related disorders; meanwhile, the early stages of the inflammatory events remain elusive. Interestingly, although the primary sequence of many gliadin peptides is well known, it was only recently revealed the self-assembly capability of two pathogenic gliadin fragments and their connection to the early stage of diseases. This review is dedicated to the most relevant biophysical characterization of the complex gliadin digest and the two most studied gliadin fragments, the immunodominant 33-mer peptide and the toxic p31-43 in connection with inflammation and innate immune response. Here, we want to emphasize that combining different biophysical methods with cellular and in vivo models is of key importance to get an integrative understanding of a complex biological problem, as discussed here.